Development of Students' Critical Thinking Skills with STEM Activities in Early Childhood Science Education - Vesile Uyulan; Serkan Aslan (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This research examines how design-based STEM (Science, Technology, Engineering, and Mathematics) activities in early childhood affect the development of critical thinking skills in preschool children aged 60-72 months. The research was conducted using an action research design. The participants of the study were determined according to the purposeful sampling method. The researcher's participants consist of 15 children attending preschool education. In the study, the Critical Thinking Skill Rubric was used as a data collection tool. With this scoring key, the students' weekly work based on STEM activities was evaluated and their developments were monitored. The study was conducted with the implementation of 8 STEM scenarios. The data of the research were scored by two different scorers. Descriptive statistics were used in the analysis of the data. In the first week, it was determined that critical thinking skills were insufficient, but a significant improvement was observed in these skills during the application process. The research results show that the students enjoyed the STEM applications, their interest levels increased, and the problems experienced during the activity process decreased. Various suggestions have been presented based on the research results.